The INFLORESCENCE DEFICIENT IN ABSCISSION-LIKE6 Peptide Functions as a Positive Modulator of Leaf Senescence in Arabidopsis thaliana - Guo, Cun; Li, Xiaoxu; Zhang, Zenglin; Wang, Qi; Zhang, Zhenbiao; Wen, Lichao; Liu, Cheng; Deng, Zhichao; Chu, Yumeng; Liu, Tao; Guo, Yongfeng (Frontiers in Plant Science, 2022)
Leaf senescence is a highly coordinated process and has a significant impact on agriculture. Plant peptides are known to act as important cell-to-cell communication signals that are involved in multiple biological processes such as development and stress responses. However, very limited number of peptides has been reported to be associated with leaf senescence. Here we report the characterization of the INFLORESCENCE DEFICIENT IN ABSCISSION-LIKE6 (IDL6) peptide as a regulator of leaf senescence. The expression of IDL6 was upregulated in senescing leaves. Exogenous application of synthetic IDL6 peptides accelerated the process of leaf senescence. The idl6 mutant plants showed delayed natural leaf senescence as well as senescence included by darkness, indicating a regulatory role of IDL6 peptides in leaf senescence. The role of IDL6 as a positive regulator of leaf senescence was further supported by the results of overexpression analysis and complementation test. Transcriptome analysis revealed differential expression of phytohormone-responsive genes in idl6 mutant plants. Further analysis indicated that altered expression of IDL6 led to changes in leaf senescence phenotypes induced by ABA and ethylene treatments. The results from this study suggest that the IDL6 peptide positively regulate leaf senescence in Arabidopsis thaliana.